(untitled) (Contemporary Mathematics, 2022)
Arterioles are pivotal console of hemodynamics as they are significant contributors to pressure. Under various physiological conditions like administration of a drug, arterioles ascertain divergent mechanical forces. The current communication discusses the effect of different shapes of copper nanoparticles inoculated as nano drugs in arterioles. The blood is assumed to be a non-Newtonian fluid and is delineated as nanofluids. The three-layer model is used for modeling the blood flow as it aptly describes the flow of blood in narrow vessels of diameter less than 100 μm. The Hamilton-Crosser model is implemented to describe the thermal conductivity of nanofluid as this model holds in accordance with experimental as well as theoretical results. The expressions are also obtained for density, thermal expansion and viscosity of the considered nanofluid. The equations are solved analytically and graphs have been plotted using MATLAB. The relative consequence of various shapes of nanoparticles like platelets, blades, cylinders and bricks is observed in temperature, velocity and flow rate. It has been investigated through the graphs that brick-shaped nanoparticles have shown a maximum rise in temperature, velocity and flow rate. And reverse results are observed for blade-shaped nanoparticles. The effect of volume fraction, heat source parameter and Grashof number have also been inspected. The considered analysis shows that a suitable shape of nanoparticle can be used to develop the nano drug according to biomedical needs.